Islamic Philosophy Of Education As A Basis To Form Spiritual Intelligence And Intellectual - Firmansah Kobandaha; Muh. Rusli; Rakhmawati Rakhmawati; Annisa Nuraisyah Annas (Journal of Scientific Interdisciplinary, 2025)
The Philosophy of Islamic Education serves as the main foundation that guides the spiritual and intellectual development of each individual. As a solid foundation, this philosophy not only acts as a conceptual framework, but also spreads into the essence of education, shaping personality, and directing the mind towards a deeper understanding of knowledge and spirituality. This article aims to contribute to a deeper understanding of how Islamic educational philosophy can be a strong foundation for forming spiritual and intellectual intelligence. The method used is descriptive qualitative with library research, this research does not need to go into the field, but simply utilizes several sources of data in this article is done by searching the literature from various sources online according to the focus of the research. Data acquisition techniques are carried out by searching online books, scientific journals, and Google Scholar sources.The results of the discussion in this article show that Islamic Education Philosophy is the basis for creating spiritual and intellectual intelligence by emphasizing the integration of Islamic values ​​in forming character through holistic education, and involving the principles and indicators of spiritual and intellectual intelligence., as well as the integration of Islamic teachings in the process of forming a balanced character and personality.